2017
DOI: 10.1155/2017/9506527
|View full text |Cite
|
Sign up to set email alerts
|

A Promising Approach to Integrally Evaluate the Disease Outcome of Cerebral Ischemic Rats Based on Multiple-Biomarker Crosstalk

Abstract: Purpose The study was designed to evaluate the disease outcome based on multiple biomarkers related to cerebral ischemia. Methods Rats were randomly divided into sham, permanent middle cerebral artery occlusion, and edaravone-treated groups. Cerebral ischemia was induced by permanent middle cerebral artery occlusion surgery in rats. To form a simplified crosstalk network, the related multiple biomarkers were chosen as S100β, HIF-1α, IL-1β, PGI2, TXA2, and GSH-Px. The levels or activities of these biomarkers in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 50 publications
1
0
0
Order By: Relevance
“…Our study found that specnuezhenide, one of the main ingredients extracted from Ligustri Lucidi Fructus, ameliorates ultraviolet-induced skin aging in mice by decreasing epidermal thickness, MDA content, and SAβgal expression, and increasing the content of collagen. Consistent with that of mice given with the ROS scavenger edaravone, 23 specnuezhenide inhibits skin photoaging-related oxidative injury, inflammation, and dermal cell apoptosis. The results above suggest that specnuezhenide is a promising candidate on protect against skin photoaging.…”
Section: Discussionsupporting
confidence: 62%
“…Our study found that specnuezhenide, one of the main ingredients extracted from Ligustri Lucidi Fructus, ameliorates ultraviolet-induced skin aging in mice by decreasing epidermal thickness, MDA content, and SAβgal expression, and increasing the content of collagen. Consistent with that of mice given with the ROS scavenger edaravone, 23 specnuezhenide inhibits skin photoaging-related oxidative injury, inflammation, and dermal cell apoptosis. The results above suggest that specnuezhenide is a promising candidate on protect against skin photoaging.…”
Section: Discussionsupporting
confidence: 62%